The Economic Value of Habits in Household Production – A Field Experiment - Ioana Bejan; Carsten Lynge Jensen; Laura Mørch Andersen; Lars Gårn Hansen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2018)
People are prone to habits but how important are they for economic outcomes? In a randomized field experiment we compare two treatments with identical economic incentives to adjust a range of household production activities. Treatments only differ in the extent to which they allow households to adjust habits relevant for these activities. We utilize smart-metered hourly power consumption to unobtrusively measure treatment effects. We find that preventing habits from being adjusted reduces consumer surplus by 76% suggesting a substantial economic value of habits.
Keywords: C93; D12; D90; 330; habits; field experiment; household behavior; text messages; electricity use